"I'm Going to Put on Bright Clothes now" The Process and Social Dimensions of Resilience Among Older Adults - Conlon, Catherine; Timonen, Virpi (My University, 2025)
This article focuses on older adults’ resilience following major losses. Interviews of seventeen older adults in Ireland illuminate the resilience process and its social dimensions – family, friends, social participation, formal supports, faith and spirituality. Becoming resilient is a process that develops through agential resolve contextualized by utilization of available resources. Those who had struggled to see themselves as resilient benefited from formal supports – such as counseling and social prescribing – that helped them to engage resilient agency. The resilience process presents as an internal resolution aided by social supports.
PUBLISHED
Keywords: Ageing; Older people, resilience, social support, Ireland; Ageing